Strategies for the development of stimuli-responsive small molecule prodrugs for cancer treatment - Tu, Yuxuan; Gong, Jianbao; Mou, Jing; Jiang, Hongfei; Zhao, Haibo; Gao, Jiake (Frontiers in Pharmacology, 2024)
Approved anticancer drugs typically face challenges due to their narrow therapeutic window, primarily because of high systemic toxicity and limited selectivity for tumors. Prodrugs are initially inactive drug molecules designed to undergo specific chemical modifications. These modifications render the drugs inactive until they encounter specific conditions or biomarkers in vivo, at which point they are converted into active drug molecules. This thoughtful design significantly improves the efficacy of anticancer drug delivery by enhancing tumor specificity and minimizing off-target effects. Recent advancements in prodrug design have focused on integrating these strategies with delivery systems like liposomes, micelles, and polymerosomes to further improve targeting and reduce side effects. This review outlines strategies for designing stimuli-responsive small molecule prodrugs focused on cancer treatment, emphasizing their chemical structures and the mechanisms controlling drug release. By providing a comprehensive overview, we aim to highlight the potential of these innovative approaches to revolutionize cancer therapy.